Richness and Taxonomic Representation of the Genus Platanus in Santiago (Chile) Based on Pcr Procedure on the Leafy Gene (Lfy-I2) [Riqueza y Representación Taxonómica del Género Platanus en Santiago (Chile) Basada en Procedimiento Pcr del Gen Lfy-I2] - Castro-Morales, S (Universidad de Concepcion, 2022)
Species of the genus Platanus are widely distributed around the globe, due to their ornamental use. Although there are 10 valid species, an undetermined number of hybrids have been generated from them. Therefore, in different cities where these taxa have been planted-including Chilean cities-the diversity and taxonomic representation of Platanus is confusing and controversial. Through a PCR-based procedure on the LEAFY gene (LFYi2), an informative gene to identify Platanus species, we analyzed the diversity of the genus in Santiago, measuring also its representation. We sampled 269 Platanus trees distributed in streets and avenues of Santiago, showing that there are at least seven taxa, including the species P. occidentalis and P. orientalis, and five hybrid taxa; one of them is P. × hispanica, while the other four have no discernible origin from Leafy-i2 (here called Platanus A, Platanus B, Platanus C and Platanus D). In terms of representation, the set of hybrid taxa accumulated 84.7% of the trees sampled; while P. orientalis and P. occidentalis together accumulated 15.3% of the trees. Of the species, P. orientalis was the most frequent (14.9%), while among the hybrids, the most frequent was Platanus A (40.8%); in contrast, P. × hispanica represented a low proportion of the sample (1.9%). These results confirm the presence of P. occidentalis, P. orientalis and P. × hispanica in Santiago; however, the cumulative representation of these three taxa (17.2%) is lower than that of undetermined hybrids (82.8%). The taxonomic recognition and representation of Platanus specimens in Santiago is an important tool for projecting future urban tree planting efforts, especially in view of the ecosystem services provided by them. © 2022 The author(s). Gayana Botánica and 2022 Universidad de Concepción.